INNOVATIONS IN THE DESIGN OF SPECIAL CLOTHING - KULESHOVA, SVITLANA; MATVIICHUK, SVETLANA; KOROL, SVITLANA; LEBEDYNSKA, OKSANA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
The article offers an approach to the popularization of innovative technologies of complex processing of polymer-containing waste into composite polymer materials and examples of their use for protective elements of special clothing. The scientific novelty of the study consists in the analysis and systematization of innovative technologies for designing special clothing with increased protective properties due to the use of composite polymer materials at all stages of creation and promotion of products to the fashion market. The practical significance lies in increasing the innovative potential of the components of design projects of modern special clothing on the example of improving the design processes of special purpose products in the conditions of ULINE LLC in Vynohradiv.The innovations of artistic and aesthetic factors include creative sketches of project images of models-ideas of men's work overalls for ULINE LLP in Vynohradiv, which were developed and proposed as a number of color solutions in the artistic system "Family" on the basis of digitalization. In order to improve the strategy of promoting the fashion brand "ULINE" of Vynogradiv and selling the models of manufactured men's work overalls on the fashion market, a database of visual transformations of images was developed for the presentation of special purpose products on the website of this company with the aim of their further integration into fashion clothing design.The innovations of the utilitarian factors of special clothing include the methods of providing workwear products of ULINE LLC, Vynohradiv, with increased wear resistance due to additional structural elements by processing them with polymer compositions. The study proposed rational methods of processing overlays with a polymer coating. Sewing equipment is selected for sealing the seams of special clothing. According to the results of research, experimental samples of men's work overalls with removable protective elements in the knee area were made in the conditions of ULINE LLC in Vynohradiv to improve the operational characteristics of the clothing.
Keywords: innovative technologies; special protective clothing; composite polymer materials; overlays